Teatralidade em cordel : experiência artística e educacional a partir da obra do cordelista Baraúna - Alcântara, Leide Rosane Silva Souza de (2018)
The present work, Teatralidade in cordel: artistic and educational experience based on Baraúna 's work investigated the theater as a pedagogical act, being guided by the introduction of cordel literature in the school context. The objective of this research was to develop a scenic creative process with the students of the second phase of elementary school, from the public school Neusa Pereira da Silva, from the cordelista literature of Baraúna. In this context, we walk with the fomentation of local art, valuing popular culture and inserting through the teaching of theater in the school, as a proposal of pedagogical theater, stimulating students to develop the individual potential that each one has and allowing the process was enriched through the direct contribution of each individual involved in the classroom experience. As a basis was used the theater triad, students and local reality. Theoretically, we study the themes of theater in education, theatrical games, string - context and history, important elements for a staging. Methodologically, this was a participatory research, directed by a qualitative approach, where for analysis of results were used techniques such as: theater workshops, theater games, conversation wheels, string readings, all culminating in the presentation of a theatrical work as a result end of the whole process developed over a year of theoretical-practical work. The conclusions make it possible to affirm that, despite the numerous difficulties encountered in teaching theater in school, we defend the teaching of the performing arts, as a necessary qualification for its importance and relevance as a pedagogical proposal, enabling the student to reflect critically and to think with the body, with the voice and with the innumerable possibilities of reading the reality of the world through the theater, thus enriching the current teaching-learning process and the formation of the new generations.